The Role of the Community in the Posyandu Program in Tambakrejo Village - Cici Ela Rohbisti; Isna Fitria Agustina (Universitas Muhammadiyah Sidoarjo, 2022)
Posyandu activities are real activities that involve community participation in health service efforts from the community, which are carried out by health cadres who have received education and training from puskesmas regarding basic health services. The role of cadres is important for the operation of Posyandu in the regions. One form of community-based health effort that is managed and implemented from, by, for and with the community in the rimplementation of health development, in order to empower the community and provide convenience to the community in obtaining basic health services, especially to accelerate the reduction of maternal and infant mortality. Efforts to develop the quality of human resources by optimizing the potential for growth and development of children can be carried out evenly, if a community-based health service system such as Posyandu can be implemented effectively and efficiently to be able to reach all targets who want services for child growth and development, pregnant women, breastfeeding mothers, and postpartum. The method used is descriptive qualitative data obtained through observation, documentation, interviews and using sources from books, journals, and policy documents. The results of this study indicate that the role of posyandu cadres in Tambak Rejo Village, Krembung District, Sidoarjo Regency has been running effectively. It can be seen from their active role in routinely socializing the posyandu program, and their participatory role in assisting people who experience health problems by providing good services, and the passive role of posyandu cadres, namely socialization without an invitation for the community to join the posyandu program in Tambak Rejo Village. Krembung District, Sidoarjo Regency.